2010
DOI: 10.1097/mop.0b013e328337685b
|View full text |Cite
|
Sign up to set email alerts
|

Immunization updates and challenges

Abstract: Pediatric providers currently face numerous challenges in improving rates of immunization among children and adolescents. Promoting coverage through the influenza vaccines, counseling parents with clear information about the risks and benefits of vaccines, and taking advantage of nonpreventive visits for immunization are some strategies suggested to address these challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Second, a well-established barrier to influenza immunization is a general lack of patient acceptance of traditional intramuscular vaccination: results obtained from recent European surveys indicate that 20% of adults and 14% of elderly patients refuse vaccination because they dislike injections or needles, considering other ways of vaccine administration an encouraging option to implement vaccination against influenza 15 - 18 …”
Section: Introductionmentioning
confidence: 99%
“…Second, a well-established barrier to influenza immunization is a general lack of patient acceptance of traditional intramuscular vaccination: results obtained from recent European surveys indicate that 20% of adults and 14% of elderly patients refuse vaccination because they dislike injections or needles, considering other ways of vaccine administration an encouraging option to implement vaccination against influenza 15 - 18 …”
Section: Introductionmentioning
confidence: 99%
“…A well-established barrier to influenza immunization is a general lack of patient acceptance of traditional intramuscular vaccination: recent studies have demonstrated that the most common reasons for missing previous vaccinations are fear of adverse events, bothered by pain during injection and dislike for injections or needles, and that other ways of vaccine administration were considered to be an encouraging alternative to implement vaccination against influenza. [12][13][14][15][16][17][18][19] For all these reasons, new vaccines providing (1) a robust, effective and protective antibody response in patients with impaired innate and adaptive immunity, such as older people or patients with chronic diseases, (2) a broader and cross-reactive immune response against drifted influenza variants and (3) an excellent safety, tolerability and acceptability profile are urgently needed. Among several strategies explored to enhance immunogenicity of plain -subunit and split -vaccines, the use of adjuvants (i.e., MF59 ® ), or carriers, (i.e., virosome), have led to licensed vaccines in Europe, while intradermal administration of influenza vaccine has emerged as a promising option, thanks to the recent availability of a new delivery device.…”
Section: Head-to-head Comparison Of An Intradermal and A Virosome Infmentioning
confidence: 99%
“…1 Current Centers for Disease Control and Prevention (CDC) guidelines recommend routine yearly influenza vaccination for all people $6 months of age, with emphasis on those who are immunosuppressed or have chronic illness. 1,12,13 Patients who are ,9 years of age who have never been immunized against influenza should receive 2 doses, 1 month apart, which is associated with a better immunologic response. 12, 14 Because the vaccine is safe and poses no risk of viral transmission, routine vaccination of the pediatric cancer population is recommended.…”
mentioning
confidence: 99%